2-Methylacrylamide as a bioisoster of thiourea group for 1, 3-dibenzylthioureido TRPV1 receptor antagonists. Issue 11 (15th June 2018) - Park, Seol Rin; Kim, Juhyun; Lee, Sun Young; Park, Young-Ho; Kim, Hee-Doo
Graphical abstract: Highlights: 1, 3-Dibenzylthioureas having methanesulfonylamide are potent TRPV1 antagonists. Thiourea moiety of 1, 3-dibenzylthioureas could be replaced to 2-methylacrylamide. This replacement enable us to design the more druggable TRPV1 related antagonists. Abstract: In order to replace thiourea group with the more drug-like moiety for 1, 3-dibenzylthioureas having TRPV1 antagonist activity, we introduced a set of functional groups between the two aromatic rings based on bioisosteric replacement. The synthesized bioisosteres of 1, 3-dibenzylthioureas were tested for their antagonist activities on TRPV1 by 45 Ca 2+ -influx assay using neonatal rat cultured spinal sensory neurons. Among the tested 14 kinds of bioisosters, 2-methylacrylamide group was the best candidate to replace thiourea group. Compound7c, 2-methylacrylamide analog of ATC-120, showed as potent as ATC-120 in its antagonist activity. In addition, 2-methylacrylamide analog7e having vinyl moiety showed the most potent activity with 0.022 μM of IC50 value, indicating that thiourea group of 1, 3-dibenzylthioureas could be replaced to 2-methylacrylamide without loss of their potencies.